2021
DOI: 10.3389/fonc.2021.628324
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Exceptional Response to Avelumab After Failure of Electrochemotherapy in a Patient With Rapidly Progressive, PD-L1-Negative Merkel Cell Carcinoma

Abstract: This case report shows, for the first time, a patient experiencing a complete response after one dose of avelumab following extensive disease progression with prior electrochemotherapy (ECT) treatment. We suggest that ECT may help to establish a tumor microenvironment favorable to immunotherapy. Merkel cell carcinoma (MCC) is a highly aggressive skin cancer with seldom durable chemotherapy responses. ECT has recently emerged as a potential treatment option for several malignancies, including MCC. Avelumab, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The survival prognosis is poor, with an expected five-year survival of only 20%, with many of the patients already having distant metastases when diagnosed. In individual patient cases [ 29 , 30 ] and in preclinical studies with both ECT with bleomycin and CaEP [ 31 , 32 , 33 , 34 ] the treatment has been shown to induce a systemic immunological response. This is interesting, as CaEP and/or ECT may hold the potential of going from a local treatment only to a systemic treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival prognosis is poor, with an expected five-year survival of only 20%, with many of the patients already having distant metastases when diagnosed. In individual patient cases [ 29 , 30 ] and in preclinical studies with both ECT with bleomycin and CaEP [ 31 , 32 , 33 , 34 ] the treatment has been shown to induce a systemic immunological response. This is interesting, as CaEP and/or ECT may hold the potential of going from a local treatment only to a systemic treatment in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Even more interesting, it has been suggested that ECT, followed by an immunological treatment, might lead to an even more convincing tumor response [ 35 ]. In a single case, a patient with highly aggressive skin cancer was treated with ECT followed by one dose of Avelumab (anti-programmed death-ligand 1 (PD-L1) monoclonal antibody) and experienced an excellent treatment response [ 30 ]. It was suggested that ECT helped to establish a favorable microenvironment in the malignant cells, which further enhanced the effect of the Avelumab.…”
Section: Discussionmentioning
confidence: 99%
“…Also, additional effort has been made to understand the prognostic and predictive potential of the NLR and LDH biomarkers in patients with MCC [123]. Torchio and his group examined an interesting case of a patient who had elevated NLR and LDH values prior to ICI treatment, followed by a rapid decrease in the levels of these markers after therapy [123]. An exceptionally complete response from the patient was reported.…”
Section: Emerging Predictive Biomarkers For Ici In Merkel Cell Carcinomamentioning
confidence: 99%